African asylum at a crossroads : activism, expert testimony, and refugee rights - Berger, Iris, 1941- (Ohio University Press, 2015)
African Asylum at a Crossroads: Activism, Expert Testimony, and Refugee Rights examines the emerging trend of requests for expert opinions in asylum hearings or refugee status determinations. This is the first book to explore the role of court-based expertise in relation to African asylum cases and the first to establish a rigorous analytical framework for interpreting the effects of this new reliance on expert testimony. Over the past two decades, courts in Western countries and beyond have begun demanding expert reports tailored to the experience of the individual claimant. As courts incre.